Impact of demographic factors on employee's perception of mobbing: A case study from a logistics company - YILDIRIM, HAKAN (ELSEVIER SCIENCE BV, 2012)
Mobbing is one of the obstacles of collaborative and effective organization that challenges motivation and peace in work place. Perceptions of employees on mobbing have critical effects on employee motivation, hence on job stress and job performance that directly affect productivity and organizational effectiveness. On the other hand, analyzing socio-demographic factors and identifying the group based differences in mobbing perceptions of employees is important for identifying the high risk groups. Differences enable policy makers to better design preventive actions in accordance with particular characteristics and needs of these groups. In this context, the purpose of this study is to explore the perceived mobbing level and impact of demographic factors and type of jobs on employees' perceptions of mobbing by using the findings of a case study in a logistics company in Turkey. For this purpose, from the theoretical background, we used a questionnaire that included basic factors that determine level of mobbing in a work place. Responses to survey were analyzed for finding out the significance of differences in terms of the demographics of participants. Therefore, understanding the impact of demographic factors and type of job on mobbing perceptions can enable human resources managers to develop relevant, specific policies that consider the characteristics of employees and jobs. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference
Keywords: Mobbing; demographic factors; logistics industry; employee perceptions; WORKPLACE